RELEVANSI PEMIKIRAN FAZLUR RAHMAN DALAM MODERNISASI PENDIDIKAN ISLAM (Studi Analisis di Madrasah Aliyah Al-Djufri Desa Blumbungan Kecamatan Larangan Kabupaten Pamekasan) - Dafiki, Abdullah; Siswanto (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
Modernization of Islamic education is an ijtihad carried out by scientists to update or change behavior, ways of thinking, understandings, customs, old institutions to new ones in accordance with the values of Islamic teachings, so that they can adapt to the times. modern. Fazlur Rahman introduced his ideas and thoughts on the renewal of Islamic education that the renewal of Islamic education can be done by accepting modern secular education, then trying to incorporate it into Islamic education in order to apply the modernized Fazlurrahman concept and the relevance of Islamic education. - Djufri Blumbungan, Pamekasan Regency, with these indicators, researchers are interested in conducting research in the Madrasah